Beraprost ameliorates postmenopausal osteoporosis by regulating Nedd4-induced Runx2 ubiquitination - Zheng, Huo-Liang (Cell Death Dis, 2021)
Bone health requires adequate bone mass, which is maintained by a critical balance between bone resorption and formation. In our study, we identified beraprost as a pivotal regulator of bone formation and resorption. The administration of beraprost promoted differentiation of mouse bone mesenchymal stem cells (M-BMSCs) through the PI3K–AKT pathway. In co-culture, osteoblasts stimulated with beraprost inhibited osteoclastogenesis in a rankl-dependent manner. Bone mass of p53 knockout mice remained stable, regardless of the administration of beraprost, indicating that p53 plays a vital role in the bone mass regulation by beraprost. Mechanistic in vitro studies showed that p53 binds to the promoter region of neuronal precursor cell-expressed developmentally downregulated 4 (Nedd4) to promote its transcription. As a ubiquitinating enzyme, Nedd4 binds to runt-related transcription factor 2 (Runx2), which results in its ubiquitination and subsequent degradation. These data indicate that the p53–Nedd4–Runx2 axis is an effective regulator of bone formation and highlight the potential of beraprost as a therapeutic drug for postmenopausal osteoporosis.